![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
高数 积分法 这几道题怎么做?
10
换元,令√[(a+x)/(a-x)]=t,则x=a(t^2-1)/(t^2+1),dx=4at/(t^2+1)^2 dt原积分
= ∫ t*4at/(t^2+1)^2 dt
=4a ∫ t^2/(t^2+1)^2 dt
=4a [∫1/(t^2+1) dt -∫1/(t^2+1)^2dt]
再换元,令t=tanu,u=arctant,dt=1/(cosu)^2。sinu=t/√(1+t^2),cosu=1/√(1+t^2)。则上式
=4a [arctant - ∫ (cosu)^2 du]
=4a [arctant - ∫ (1+cos2u)/2 du]
=4a [arctant - u/2-sin2u/4 +C]
=2a [2arctant - u-sinucosu +C]
=2a [2arctant - arctant-t/(1+t^2) +C]
=2aarctan√[(a+x)/(a-x)]-√(a^2-x^2) + C
13∫e^(ax)sinbxdx=
=-1/b∫e^(ax)dcosbx
=-1/b*e^(ax)cosbx+1/b∫cosbxde^(ax)
=-1/b*e^(ax)cosbx+a/b∫cosbxe^(ax)dx
=-1/b*e^(ax)cosbx+a/b²∫e^(ax)dsinbx
=-1/b*e^(ax)cosbx+a/b²*e^(ax)sinbx-a/b²∫sinbxde^(ax)
=-1/b*e^(ax)cosbx+a/b²*e^(ax)sinbx-a²/b²∫e^(ax)sinbxdx
所以
(1+a²/b²)∫e^(ax)sinbxdx=-1/b*e^(ax)cosbx+a/b²*e^(ax)sinbx
(a²+b²)∫e^(ax)sinbxdx=-be^(ax)cosbx+ae^(ax)sinbx
所以∫e^(ax)sinbxdx=[-be^(ax)cosbx+ae^(ax)sinbx]/(a²+b²)+C
15
令x=tant,t∈(-π/2,π/2),x²=tan²t,dx=dtant=sec²tdt
1/x=cott,1/x²=cot²t,1+1/x²=1+cot²t,(1+x²)/x²=csc²t,√(1+x²)/x=csct
∫1/x²√(1+x²)dx
=∫sec²t/tan²t√(1+tan²t)dt
=∫sec²t/tan²t√sec²tdt
=∫sec²tcos²t/sin²tsectdt
=∫cost/sin²tdt
=∫1/sin²tdsint
=-1/sint+C
=-csct+C
=-√(1+x²)/x+C
先采纳了吧,有不懂的可以追问,或者百度hi
广告 您可能关注的内容 |